Modeling activity in the field of spatial relations in Early Childhood Education (Edma 0-6: Educación Matemática en la Infancia, 2021)
In this paper we will show, first of all, how the educational system does not take charge of the teaching of the spatial competencies every citizen needs for its daily life. Secondly, we will outline differences between spatial knowledge and geometric knowledge, according to their genesis, vocabulary, structure and validation. Thirdly, we describe the analogic and geometrical modeling activity of space, showing that both allow connections between two worlds: the sensitive world and a model of this. Both worlds include different internal rules, with different formalization levels. Finally, we introduce a collection of didactic situations for preschool. The aim of these situations is to get pupils involved in an analogic modeling activity of space, and even a first approach to geometric modeling.
Keywords: Space-geometric modeling; Early Childhood Education; Didactic situations